2016
DOI: 10.1016/j.outlook.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of state nurse practitioner scope-of-practice regulation on health care delivery: Systematic review

Abstract: a b s t r a c tBackground: One proposed strategy to expand primary care capacity is to use nurse practitioners (NPs) more effectively in health care delivery. However, the ability of NPs to provide care to the fullest extent of their education is moderated by state scope-of-practice (SOP) regulations. Purpose: The purpose of this study was to examine the impact of state SOP regulations on the following three key issues: (a) NP workforce, (b) access to care and health care utilization, and (c) health care costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
118
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 33 publications
4
118
0
2
Order By: Relevance
“…The Changing Regulatory Environment tends to be addressed least, and is often cited as a barrier to change (Figueroa ; Xue et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The Changing Regulatory Environment tends to be addressed least, and is often cited as a barrier to change (Figueroa ; Xue et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Further, fewer restrictions on the scope of practice for nurse practitioners is associated with an increase in the number of nurse practitioners practicing in rural or medically underserved populations. 38 Nurse practitioner-physician comanagement in rural or medically underserved populations allows primary care physicians to free time up for additional appointments, as well as provide patients with more one-on-one time during patient visits to address individual patients' needs.…”
Section: Consequences Of Comanagementmentioning
confidence: 99%
“…While the authors found that NP autonomy was associated with an increase in the number of NPs and expanded health care utilization, none of the included studies examined quality of care as the primary outcome (Xue et al. ). This study is intended to fill this gap.…”
mentioning
confidence: 99%